2016
DOI: 10.1080/21505594.2016.1139280
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of the apoptosis pathway by theCoxiella burnetiieffector protein CaeA requires the EK repetition motif, but is independent of survivin

Abstract: ABSRTACT Coxiella burnetii is an obligate intracellular bacterium that causes Query (Q) fever, a zoonotic disease. It requires a functional type IV secretion system (T4SS) which translocate bacterial effector proteins into the host cell cytoplasm and thereby facilitates bacterial replication. To date, more than 130 effector proteins have been identified, but their functions remain largely unknown. Recently, we demonstrated that one of these proteins, CaeA (CBU1524) localized to the host cell nucleus and inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 50 publications
0
49
0
Order By: Relevance
“…To gain further insight into AnkG function, we compared the anti‐apoptotic activities of AnkG alleles from different C. burnetii species. It had already been suggested that this might lead the path to characterizing effector proteins in more detail (Bisle et al ., ). We first analysed, whether the expression of AnkG from C. burnetii Nine Mile (AnkG NM ), which was used in all previous studies, exhibited a different anti‐apoptotic activity than the AnkG allele from C. burnetii Dugway (AnkG Dug ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…To gain further insight into AnkG function, we compared the anti‐apoptotic activities of AnkG alleles from different C. burnetii species. It had already been suggested that this might lead the path to characterizing effector proteins in more detail (Bisle et al ., ). We first analysed, whether the expression of AnkG from C. burnetii Nine Mile (AnkG NM ), which was used in all previous studies, exhibited a different anti‐apoptotic activity than the AnkG allele from C. burnetii Dugway (AnkG Dug ).…”
Section: Resultsmentioning
confidence: 97%
“…To gain further insight into AnkG function, we compared the anti-apoptotic activities of AnkG alleles from different C. burnetii species. It had already been suggested that this might lead the path to characterizing effector proteins in more detail (Bisle et al, 2016). We first analysed, whether the expression of AnkG from C. A. AnkG 1-42 (20 μg) and p32 (37.5 μg) were incubated overnight on ice, equal to a molar ratio of 3:1.…”
Section: Ankg Dug Display Increased Anti-apoptotic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…It potentially facilitates cell cycle processes and cell division and reduces apoptotic indices, which is strongly related with poor prognosis in breast cancer [13, 14]. Transcription from the survivin gene locus gives rise to 5 splice variants [15].…”
Section: Introductionmentioning
confidence: 99%
“…A similar screen of known Coxiella effectors identified CBU1524 (CaeA) and CBU1532 (CaeB) as antiapoptotic effectors [87,126]. CaeA localizes to the nucleus and reduces both intrinsic and extrinsic apoptotic cascades between the initiator caspase-9 and the executioner caspase-7 by a mechanism requiring a CaeA glutamate/lysine repeat region [127]. More potent inhibition of intrinsic apoptosis is observed with CaeB that localizes to mitochondria and blocks mitochondrial outer membrane permeabilization in response to staurosporine treatment by a mechanism independent of p32 [126].…”
Section: The Hard Part: Effector Functionmentioning
confidence: 99%